Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Metro Futsal Renon Denpasar - Pratiwi, Pipit Ingka; Seminari, Ni Ketut (E-Jurnal Manajemen; Vol 3 No 6 (2014), 2014)
His research has the objective to determine the effect of service quality on customer satisfaction and determine the dominant variables that affect customer satisfaction Metro Futsal. Analysis of the data used is a Method of Successive Internal (MSI) and multiple linear regression analysis. The results analysis coefficient of determination (R 2 ) unknown amount of 0.779. It shows that 77.9% of variation changes the variable rise and fall of consumer satisfaction is influenced by the variable quality of service, while the remaining 22.1% is influenced by other variables not included in the model. The results of this study showed a significant effect simultaneously and partially between service quality on customer satisfaction Metro Futsal. Keyword: quality of service, customer satisfaction.
Keywords: quality of service: customer satisfaction